Smart move sistema de captura de movimiento (2020)
The project is proposed as a training alternative within the movement arts context. This, represented by an objectual system manipulated by practitioners, aims to improve the efficiency of specific trainings by increasing the understanding of each movement ánd decreasing the necessary repetitions established far mastering it. To achieve this, we go to the judicious study of the execution of specific movements in the context of dance, acrobatics, circus practices and yoga, this from the observation of training and data collection through surveys, to then confront theoretical infarmation with practice in order to meet the needs of users using technology. Smart Move, is a movement capture system designed far those who need instruction and who haven't met expectations about their trainings. This system addresses a learning methodology of movement techniques that allows the user to learn at their own rhythm and appropriate the studied technique, thanks to a central that synchronizes nodes that are located in the body and that, with the help of a screen, allow to visualize and guide a series of movements. This product is designed to compete optimally in the market of mocap systems, beca use it is cheaper than other inertial unit systems, it's far personal use and its design allows to customize and assemble easily.